International year of indigenous languages (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2019)
The year 2,019 was declared as the international year of the Indigenous Languages, reason for which the world has turned to the search of strategies and measures that allow to safeguard them. The statistics reveal significant figures of the danger of extinction in which they find themselves and with them the socio-cultural legacy that identifies them as a people would be lost. Venezuela does not escape this reality, UNESCO registers in its Atlas 34 Venezuelan languages ​​at risk of disappearing. Linguists and students of related subjects struggle to provide solutions and preserve them through written works, but it is necessary that government policies are devoted to safeguard and protect the linguistic heritage of our ethnic groups. That is why what Venezuelan anthropologist Esteban Monsonyi (2017) expressed when he said "the planet and our country are in danger ... I feel part of that indigenous people and as such I have to protest this humanity, forgotten, oppressed". This corroborates that the indigenous peoples live in the state's helplessness despite knowing that they were included in the 1999 Constitution, where indigenous rights and their contribution to the nation are recognized.